Use of alcohol, tobacco, cannabis and other drugs in adolescence: Effects of family and neighborhood - Fuentes, María C.; Alarcón, Antonio; García, Fernando; Gracia, Enrique (Anales de Psicología / Annals of Psychology, 2015)
The aim of this study was to analyze the protective or risk factors of parental educational styles for the consumption of alcohol, tobacco, cannabis and other drugs, considering the interaction of parenting styles with the dangerousness of the neighborhood. Based on the responses of 628 adolescents, 369 females (58.8%) and 259 males (41.2%) between 15 and 17 years old (M = 16.03 years old, SD = 0.79 years old), families were classified according to their educational style (authoritative, indulgent, authoritarian or neglectful) and their level of perceived neighborhood risk (high or low). Results showed no interaction effect; however, main effects of educational styles and perceived neighborhood risk were obtained. Adolescents from indulgent families showed the lowest consumption in the substances evaluated, while those from authoritative, authoritarian and neglectful families showed the highest consumption. Moreover, adolescents from high-risk neighborhoods obtained the highest consumption. Indulgent educational style, acting primarily through affection and not imposition, works as a protective factor regardless of the danger in the neighborhood. The importance of encouraging this parental performance in prevention and intervention programs is highlighted, promoting specific educational strategies to improve affection, communication and parental involvement.